The learning trajectory of emerging professionalism: A Finnish student teacher negotiating world-view education and early childhood education and care superdiversity. (December 2020) - Lamminmäki-Vartia, Silja; Poulter, Saila; Kuusisto, Arniika
This article examines the learning trajectory of the emerging professionalism of Finnish early childhood education and care student teachers, focusing in particular on their professionalism in early childhood education and care world-view education in the context of cultural and world-view superdiversity. Of specific interest here is what students postulate as meaningful in their professional learning processes and why, and what kinds of directions this value-learning process has taken. The data was generated over a year-long learning process in a group with seven early childhood education and care students and six in-service early childhood education and care teachers through survey responses, reflective learning diaries and retrospective in-depth interviews with the students. Using the Kuusisto and Gearon (2017a) value-learning-trajectory model as an analytical tool, the findings are presented through an in-depth case study depicting one student's learning throughout the process and across the data sets. To conclude, the conceptual working model is developed further to depict the development of emergent early childhood education and care teacher professionalism with a particular focus on world-view education and early childhood education and care superdiversity.